2017
DOI: 10.1016/j.nlm.2017.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning with spatio-temporal patterns: Constraining the contribution of the hippocampus to configural learning

Abstract: The conditions under which the hippocampus contributes to learning about spatio-temporal configural patterns are not fully established. The aim of Experiments 1-4 was to investigate the impact of hippocampal lesions on learning about where or when a reinforcer would be delivered. In each experiment, the rats received exposure to an identical set of patterns (i.e., spotted+morning, checked+morning, spotted+afternoon and checked+afternoon); and the contexts (Experiment 1), times of day (Experiment 2), or their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…For example, in a brain imaging study with humans, Duncan et al (2018) found significant hippocampal activation associated with learning configural information. However, hippocampal lesions in the rat failed to influence performance in a Spatio-temporal learning task that was contingent upon the configuration between context and time of day (Dumigan et al, 2017). In fact, based upon such failures, some have even argued that dissociation of elemental vs. configural learning processes may be impossible, both at the level of behavioral analysis and the level of neurobiological mechanisms, as the configural aspect of the task may be viewed as resulting from combining two or more single elements into a compound element that then is treated by the learning system as if it was one cue (reviewed in Honey et al, 2014), a hypothesis that is, in its essence, similar to the theory of chunking (e.g., Capaldi et al, 1986).…”
Section: Elemental Vs Configural Learning In Context and Cue Dependent Fear Conditioningmentioning
confidence: 97%
“…For example, in a brain imaging study with humans, Duncan et al (2018) found significant hippocampal activation associated with learning configural information. However, hippocampal lesions in the rat failed to influence performance in a Spatio-temporal learning task that was contingent upon the configuration between context and time of day (Dumigan et al, 2017). In fact, based upon such failures, some have even argued that dissociation of elemental vs. configural learning processes may be impossible, both at the level of behavioral analysis and the level of neurobiological mechanisms, as the configural aspect of the task may be viewed as resulting from combining two or more single elements into a compound element that then is treated by the learning system as if it was one cue (reviewed in Honey et al, 2014), a hypothesis that is, in its essence, similar to the theory of chunking (e.g., Capaldi et al, 1986).…”
Section: Elemental Vs Configural Learning In Context and Cue Dependent Fear Conditioningmentioning
confidence: 97%